Shoulder joint angle errors caused by marker offset - Zhang, Z.; Halkon, B.; Chou, S. M.; Qu, X. (Procedia Engineering, 2015)
The International Society of Biomechanics (ISB) has recommended a standardization of the definition of the joint coordinate system (JCS) and use of a sequential rotation to describe human shoulder joint rotation. Markers attached to the surface of the body may move during the process of motion data capture, resulting in an offset from their initial location. This leads to a change of the JCS and therefore affects the calculated shoulder joint angles. In this research study, we presented a simple marker offset model to quantify the shoulder joint errors for both static poses and dynamic activities. Specific conditions of different offsets and elbow flexion angles were studied. Results showed that the errors should not be neglected when the shoulder elevation angle was near -90° and 90°, or elbow flexion was very small. Attention should be paid to these errors for such activities especially walking and throwing.